Features of formation of the military personnel’s morbidity of acute respiratory infections of the upper respiratory tract - A. E. Zobov; A. A. Panov; A. A. Kuzin; A. A. Kucherov; S. N. Nikishov; E. N. Kolosovskaya; S. V. Artebyakin (Журнал инфектологии, 2020)
The article sets out the views on the causes of the incidence of various categories of military personnel with acute respiratory infections of the upper respiratory tract (hereinafter – ARI URT), as having the greatest military and epidemiological significance for almost all military contingents.According to the results of a study of literature data, two groups of reasons for the formation of the incidence of acute respiratory infections of the airborne diseases are identified: external (associated with the exposure of military personnel to specific factors of military service) and internal (associated with the characteristics of individual susceptibility to this group of infections).Based on the results of a retrospective epidemiological analysis of the incidence of military servicemen on conscription, the development features of the epidemic process of ARI URT in military units and compounds are shown.According to the results of a retrospective epidemiological analysis of the incidence rate of cadets at the S.M. Kirov Military Medical Academy for 2011-2017 and a comparative analysis of the reversal rate for completed cases, the presence and relatively stable proportion of military personnel exposed to frequent ARI diseases of the airborne diseases throughout the entire 6-year period has been shown period of study.The results of a combined socio-psychological study in groups of often and rarely ill cadets are shown, showing individual signs and psychological characteristics, according to which individual military personnel can be assigned to the risk contingents of increased susceptibility to ARI URT for the purpose of organizing personalized sanitary-antipyretic (preventive) measures.